Violent democracies in Latin America - Arias, Enrique Desmond; Goldstein, Daniel M., 1965- (Cultures and practice of violence series., 2010)
Collection asks why, despite the democratization of Latin American societies, multiple forms of violence have proliferated in recent years, exploring how various actors use violence to contest ideas of order, rights, citizenship, and justice.